2015
DOI: 10.1016/j.bone.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling mediates woven bone formation and vascularization during stress fracture healing

Abstract: Hedgehog (Hh) signaling is critical in developmental osteogenesis, and recent studies suggest it may also play a role in regulating osteogenic gene expression in the post-natal setting. However, there is a void of studies directly assessing the effect of Hh inhibition on post-natal osteogenesis. This study utilized a cyclic loading-induced ulnar stress fracture model to evaluate the hypothesis that Hh signaling contributes to osteogenesis and angiogenesis during stress fracture healing. Immediately prior to lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 41 publications
2
25
2
1
Order By: Relevance
“…This result is consistent with a previous study, wherein we noted that GDC treatment significantly reduced expression of osteogenic genes and periosteal bone formation in normal rat ulnae (i.e., not subjected to mechanical injury) [28]. These findings are also consistent with the findings of Ohba et al [36], who reported that treatment of mice with a Hh inhibitor (cyclopamine, a Smo antagonist) decreased bone formation and bone mass.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result is consistent with a previous study, wherein we noted that GDC treatment significantly reduced expression of osteogenic genes and periosteal bone formation in normal rat ulnae (i.e., not subjected to mechanical injury) [28]. These findings are also consistent with the findings of Ohba et al [36], who reported that treatment of mice with a Hh inhibitor (cyclopamine, a Smo antagonist) decreased bone formation and bone mass.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, deletion in the osteoblast lineage (using Col1Cre) significantly reduced the callus bone volume at day 28, indicating arole for osteoblastic Hh signaling in bone formation during fracture healing. Consistent with this latter result, we previously found that the Smo antagonist GDC-0449 diminished intramembranous bone formation after stress fracture [28]. Taken together, the previous studies indicate the Hh may play a role in osteogenesis during bone healing.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As for its specific role for bone and vessel co-regeneration, expressed by MSCs, IHH has been confirmed to be overexpressed during the repair and regeneration of bone, indicating its specific role of bone regeneration [64]. At the same time, during the regeneration of bone, together with GLI1 as we have analyzed above, our predicted gene IHH has also been confirmed to contribute to vascularization mediating by hedgehog signaling pathway [65]. As we have mentioned above, MET (ENSP00000317272) has been confirmed to participate in the co-regeneration of bone and nerve [51,52].…”
Section: Co-regeneration Genes For Bone and Vesselmentioning
confidence: 70%